Binocular rivalry and neutral dynamics - Blake, Randolph; Lee, Sang-Hun; Heeger, David (Psichologija, 2008)
The Gestalt psychologists were fascinated with dynamics evident in visual perception, and they theorized that these dynamics were attributable to ever-changing electrical potentials within topographically organized brain fields. Dynamic field theory, as it was called, was subsequently discredited on grounds that the brain does not comprise a unitary electrical field but, instead, a richly interconnected network of discrete computing elements. Still, this modern conceptualization of brain function faces the challenge of explaining the fact that perception is dynamic in space and in time. To pursue the question of visual perception and cortical dynamics, we have focused on spatio-temporal transitions in dominance during binocular rivalry. We have developed techniques for initiating and measuring these transitions psychophysically and for measuring their neural concomitants using functional magnetic resonance imaging (fMRI). Our findings disclose the existence of waves of cortical activity that travel across the retinotopic maps that define primary and secondary visual areas within the occipital cortex, in correspondence with the subjective perception of spreading waves of dominance during binocular rivalry. This paper reviews the results from those studies.